Conversor NPC-B2B com controle vetorial preditivo de corrente acionando um MIT - Oliveira, Victor Manuel Riva de (2021)
Power electronics devices are widely used in several areas. Currently, most of the electrical energy, before reaching the final consumer, is processed by these devices. In this scenario, with high demand for better power quality and more sustainable energ